2021
DOI: 10.1128/jvi.02284-20
|View full text |Cite
|
Sign up to set email alerts
|

Insight into Vaccine Development for Alphacoronaviruses Based on Structural and Immunological Analyses of Spike Proteins

Abstract: Coronaviruses that infect humans belong to the Alpha-coronavirus (including HCoV-229E) and Beta-coronavirus (including SARS-CoV and SARS-CoV-2) genera. In particular, SARS-CoV-2 is currently a major threat to public health worldwide. The spike (S) homotrimers bind to their receptors via the receptor-binding domain (RBD), which is a major target to block viral entry. In this study, we selected Alpha-coronavirus (HCoV-229E) and Beta-coronavirus (SARS-CoV and SARS-CoV-2) as models. Their RBDs exist two different … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The S1 subunit of Spike in Alphacoronaviruses has been shown to play important functional roles in host cellular interactions ( Li and Goff 2015 ) and immune evasion ( Shi et al. 2022 , 2021 ). Yang et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The S1 subunit of Spike in Alphacoronaviruses has been shown to play important functional roles in host cellular interactions ( Li and Goff 2015 ) and immune evasion ( Shi et al. 2022 , 2021 ). Yang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Protein binding functionality is often contained within the CTD of the S1 subunit, which usually occurs within the RBD ( Li and Goff 2015 ). Shi et al (2021) examined the Spike structure of CoVs and remarked on the ‘lying’ vs. ‘standing’ (‘up’ vs. ‘down’, respectively) orientation of the RBD, where the Alphacoronaviruses studied had a ‘lying’ or ‘down’ RBD orientation. The group showed that an intact NTD from the Spike of HCoV-229E, an Alphacoronavirus , was essential for producing effective neutralizing antibodies (NAbs), compared to the Spike’s with a ‘standing’ or ‘up’ RBD that could generate effective NAbs from the RBD alone.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, HCoV-229E has a low prevalence in this area. As a result, most of population has no immunity to these two viruses ( 24 ). Thirdly, adenoviruses are non-enveloped viruses that are unusually resistant to physical and chemical agents, which gives them prolonged survival capacity in various environments ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…SPR is a powerful tool for real-time, label-free measurement of binding affinity and kinetics, and the vast majority of papers citing the use of the OpenSPR fit neatly underneath this umbrella [ 3 , 5 , 7 , 9 , 15 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ,…”
Section: Binding Affinity and Kineticsmentioning
confidence: 99%
“…Researchers have used this technique to assess the binding affinity and kinetics of potential new therapeutics and affinity reagents, to study aggregation, to perform competition studies or inhibition assays, and other applications. OpenSPR has been leveraged to study diverse biochemical questions, including critical problems in human health such as Alzheimer’s disease (AD) [ 43 , 44 , 45 , 46 ], non-small cell lung cancer (NSCLC) [ 47 , 48 , 49 , 50 , 51 ], and COVID-19 [ 34 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ]. This paper provides the first comprehensive review of the literature reporting the use of the OpenSPR.…”
Section: Introductionmentioning
confidence: 99%